PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP PENGGUNGKAPAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) : SEKTOR BARANG KONSUMEN PRIMER - Achmad Rifa’i; Sri Handayani (Diponegoro Journal of Accounting, 2025)
This study examines the impact of board characteristics on the disclosure of Sustainable Development Goals (SDGs) in primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The analysis focuses on female board composition, board size, board independence, board meeting frequency, and expertise diversity, grounded in the Upper Echelons Theory, which posits that top management characteristics influence corporate strategic decisions, including sustainability disclosures.The research employs multiple linear regression analysis to assess the relationship between these board characteristics and SDGs disclosure. The results indicate that female board composition, board size, board independence, and board expertise diversity significantly affect SDGs disclosure, while board meeting frequency does not demonstrate a meaningful impact.These findings underscore the importance of gender diversity, larger board sizes, independence, and expertise diversity within boards in enhancing corporate sustainability transparency. This suggests that diverse and independent boards are more inclined to support comprehensive sustainability reporting, contributing to better corporate accountability.